Effect of Brassica oleracea in rats skin wound healing - Rebolla,Aline (2013)
PURPOSE: To investigate the effect of Brassica oleracea herbal balsam on the healing of skin wounds in rats. METHODS: Twenty four rats (Wistar, 60 days, 250 g) were divided into four groups: untreated animals (C) and treated with the ointment (T), subdivided into two experimental times (seven and 16 days). A 3cm² skin wound was made in the back of all animals. 100 ml of the Brassica oleracea was applied twice a day in T group. Biometric analysis was made with images captured at one, four, seven, ten, 13, and 16 days. At seven and 16 days, animals of each group were euthanized. The wound area removed was processed for histological and histomorphometric analysis to quantify birefringent collagen fibers. Statistical analysis was made considering p < 0.05 as significant. RESULTS: Biometric analysis revealed no significant differences between groups in both experimental times studied. However, histomorphometric analysis showed that the number of type I collagen fibers was significantly higher in the specimens of the group T16 compared to the other groups. CONCLUSION: Brassica oleracea accelerated the wound healing process increasing the number of type I collagen fibers and the maturity of the newly formed tissue.